2012
DOI: 10.5301/jn.5000144
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exercise test recovery indices and psychological and quality-of-life status in hemodialysis patients: a pilot study

Abstract: In conclusion, in HD patients, recovery indices following maximal and submaximal exercise tests were shown to provide useful indications of the patients' psychological and quality-of-life profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
1
0
2
Order By: Relevance
“…Previous studies have strongly suggested that patients with chronic kidney disease on hemodialysis are traditionally described as suffering from reduced health-related quality of life owing to general fatigue, exertional dyspnea during everyday activities, frequent hospitalizations, frustration, anxiety and depression [1,4,6].Thus regarding the evaluation of the effect of an aquatic exercise program to the quality of life of hemodialysis patients, a significant improvement was reported to the exercise group compared to control group. Similar finding have been ascertained in prior studies [4,25,38,39]. It is important to be noted that in exercising patients both parameters of SF-36 questionnaire were improved, physical and mental, while in controls there has been deterioration.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have strongly suggested that patients with chronic kidney disease on hemodialysis are traditionally described as suffering from reduced health-related quality of life owing to general fatigue, exertional dyspnea during everyday activities, frequent hospitalizations, frustration, anxiety and depression [1,4,6].Thus regarding the evaluation of the effect of an aquatic exercise program to the quality of life of hemodialysis patients, a significant improvement was reported to the exercise group compared to control group. Similar finding have been ascertained in prior studies [4,25,38,39]. It is important to be noted that in exercising patients both parameters of SF-36 questionnaire were improved, physical and mental, while in controls there has been deterioration.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, this study showed that the HRR, which reflects parasympathetic activation, was associated with blood pressure instability during HD. The HRR also reflects cardiac parasympathetic activation both in healthy individuals and patients with chronic conditions [26,27], and HD patients have lower HRRs than healthy control subjects [28]. In 2286 healthy subjects, the HRR showed a significant correlation with exercise tolerance and resting SBP [7].…”
Section: Discussionmentioning
confidence: 99%
“…O VO2pico é o parâmetro considerado padrão-ouro para avaliar a capacidade do sistema cardiovascular de captar, distribuir e usar o oxigênio. Nos pacientes em hemodiálise, há estudos com valores variam entre 15,2-22,9 mL/kg/min, bem abaixo do previsto para idade, fato que também ocorreu no presente estudo (GREGORY et al, 2011;SAMARA et al, 2012;FASSBINDER et al, 2015;HOWDEN et al, 2015).…”
Section: Discussionunclassified
“…Outro aspecto importante são os prejuízos relacionados à qualidade de vida devido à influência direta da realização da hemodiálise nas atividades da vida diária e na percepção do bem-estar individual (COSTA; VASCONCELOS; TASSITANO, 2010). Alguns estudos (COSTA; VASCONCELOS; TASSITANO, 2010;SAMARA et al, 2012;MAZAIRAC et al, 2011) que avaliaram a qualidade de vida indicaram que as dimensões mais afetadas foram o funcionamento físico, a vitalidade, a função sexual, o componente mental e a capacidade de trabalho, enquanto as dimensões relacionadas à satisfação do paciente com o tratamento, com a equipe de diálise e a interação social apresentaram os maiores escores (AL-JUMAIH et al, 2011). A avaliação da AC e da qualidade de vida está presente em muitos estudos como parâmetro de avaliação de intervenções e para prever taxa de sobrevivência (SIETSEMA et al, 2004;SAMARA et al, 2012;NELSON et al, 2016), mas, ainda não está esclarecida a relação entre AC e qualidade de vida nos pacientes em hemodiálise.…”
Section: Introductionunclassified